Institutional profile: translational pharmacogenomics at the Icahn School of Medicine at Mount Sinai. (October 2017) - Scott, Stuart A; Owusu Obeng, Aniwaa; Botton, Mariana R; Yang, Yao; Scott, Erick R; Ellis, Stephen B; Wallsten, Richard; Kaszemacher, Tom; Zhou, Xiang; Chen, Rong; Nicoletti, Paola; Naik, Hetanshi; et al.
For almost 50 years, the Icahn School of Medicine at Mount Sinai has continually invested in genetics and genomics, facilitating a healthy ecosystem that provides widespread support for the ongoing programs in translational pharmacogenomics. These programs can be broadly cataloged into discovery, education, clinical implementation and testing, which are collaboratively accomplished by multiple departments, institutes, laboratories, companies and colleagues. Focus areas have included drug response association studies and allele discovery, multiethnic pharmacogenomics, personalized genotyping and survey-based education programs, pre-emptive clinical testing implementation and novel assay development. This overview summarizes the current state of translational pharmacogenomics at Mount Sinai, including a future outlook on the forthcoming expansions in overall support, research and clinical programs, genomic technology infrastructure and the participating faculty.